ڕۆڵى بەرنامە تەندروستیە تەلەفزیۆنیەکان لە بڵاوکردنەوەى هۆشیارى تەندروستیدا - محمد, سلام نصرالدین; محمد, شاكار عبدالقادر (Sulaimani Journal for Humanities, 2021)
This thesis is based on practical researches on one of the most important areas of human interest which are health awareness. Nowadays, there are many TV programs on health awareness on most locals and satellite TV channels to give awareness upon health protection. The aim of the researcher is to discover the role of health programs and their impact & influence on viewers. Therefore, the researcher wants to illustrate the role of a health awareness TV program which is one of the most effective programs for the viewer. Furthermore, the researcher assumes the issue as a scientific matter; she strives to find out the impact of the TV programs on the viewers. The research method used is a descriptive research method, which is the most applicable method in the related field. Therefore, the most prominent aims to discover within this research are the following: 1. To find out the viewers’ interests in the health programs. 2. To find out the importance of the health program contents. 3. The purpose of the health programs in relation to health awareness. 4. To discover the TV programs based on raising awareness about during COVID- 19 pandemic in Kurdistan Region. To achieve the aims of this research. The researcher took a survey to obtain the applicants’ points of view based on (Probability Sample) method in Sulaymaniyah city center without considering their demographics, backgrounds, and professional differences. Therefore, the conclusion of this research is the following: 1. TV programs based on health have an important role in raising awareness, particularly during the COVID- 19 pandemics. 2. The viewers of TV health programs have a preference for accurate information from credible sources. Therefore, through the programs, the viewers attempt to gather as much information as possible from the program. 3. The current TV health programs that are broadcasted are beneficial and help in raising health awareness and address health concerns to their viewers 4. . The aim of the TV health programs is to help increase health awareness for the viewers and their families